A numerical model for fatigue effects in whole-body human exercise. Issue 1 (2nd January 2016) - Eriksson, Anders; Holmberg, Hans-Christer; Westerblad, Håkan
Abstract : A physiology-based fatigue model was developed and tested, with the long-term objective to study optimal pacing strategies in cross-country skiing. The model considers both aerobic and anaerobic power contributions, with different demands for carbohydrate fuel. The fatigue model accumulates traces from anaerobic efforts, and dissipates fatigue exponentially. The current fatigue value affects the effective work rate output. A limited reservoir of fuel is considered. This paper discusses the numerical formulations. Examples show the relevance of the model for basic regimes of power output, and give qualitatively relevant results, but demonstrate the need for individual physiological parameters. Further examples study the model's predictions with respect to interval training strategies, with conclusions on work rates and interval lengths.